Comparative assessment of NCEP and ECMWF global datasets and numerical approaches on rough sea ship navigation based on numerical simulation and shipboard measurements. (August 2020) - Chen, Chen; Sasa, Kenji; Ohsawa, Teruo; Kashiwagi, Masashi; Prpić-Oršić, Jasna; Mizojiri, Takaaki
Abstract: Long-term shipboard measurements of vessel performance in actual seas and practical guidance for proper ship operations in rough sea conditions are of great importance for a safe, economical and environment-friendly optimum ship routing. Data was collected from a bulk carrier during 2010–2016 covering both the Southern and Northern Hemispheres with high seasonal variability. Using the meteorological and wave models, the Weather Research and Forecasting Model (WRF) and WAVEWATCH III (WW3), numerical simulations of the weather and sea state were conducted for eight rough sea cases using the grid point value (GPV) datasets NCEP-FNL and ERA-Interim. Model results were validated by shipboard measurements and ship motion calculations. Results show a better performance of NCEP-FNL on generating high ocean surface wind speed of heavy weather than that of the ERA-Interim, while the ERA-Interim tends to perform better for generation of wind direction. Besides, utilization of a high-resolution WRF model tends to increase the accuracy of wind simulations for extremely high and low wind speed cases when compared to the linear interpolation of GPV datasets, which tends to perform better for relatively modest wind speed conditions. Results also suggest that, to achieve an optimum ship routing considering safety, cost and emission reduction; it should use the high-resolution WRF model with NCEP-FNL initial and boundary conditions to generate ocean surface winds, followed by the WW3 wave model to generate ocean surface waves for the most accurate performance in heavy weather.